Sialoadhesin promotes neuroinflammation‐related disease progression in two mouse models of CLN disease. Issue 5 (17th January 2016) - Groh, Janos; Ribechini, Eliana; Stadler, David; Schilling, Tim; Lutz, Manfred B.; Martini, Rudolf
Abstract : CLN diseases are mostly fatal lysosomal storage diseases that lead to neurodegeneration in the CNS. We have previously shown that CD8+ T‐lymphocytes contribute to axonal perturbation and neuron loss in the CNS of Ppt1 −/− mice, a model of CLN1 disease. We now investigated the role of the inflammation‐related cell adhesion molecule sialoadhesin (Sn) in Ppt1 −/− and Cln3 −/− mice, a model of the most frequent form, CLN3 disease. Microglia/macrophages in the CNS of both models showed an upregulation of Sn and markers for proinflammatory M1 polarization and antigen presentation. Sn+ microglia/macrophages associated with SMI32+ axonal spheroids and CD8+ T‐lymphocytes. To analyze their pathogenic impact, we crossbred both models with Sn ‐deficient mice and scored axonal degeneration and neuronal integrity using immunohistochemistry, electron microscopy and optical coherence tomography. Degenerative alterations in the retinotectal pathway of Ppt1 −/− Sn −/− and Cln3 −/− Sn −/− mice were significantly reduced. Ppt1 −/− Sn −/− mice also showed a substantially improved clinical phenotype and extended lifespan, attenuated numbers of M1‐polarized microglia/macrophages and reduced expression levels of proinflammatory cytokines. This was accompanied by an increased frequency of CD8+CD122+ T‐lymphocytes in the CNS of Ppt1 −/− Sn −/− mice, the regulatory phenotype of which was demonstrated by impaired survival of CD8+CD122− effector T‐lymphocytes in co‐culture experiments. We show for the first time that increased Sn expression on microglia/macrophages contributes to neural perturbation in two distinct models of CLN disease. Our data also indicate that a rarely described CD8+CD122+ T‐cell population can regulate the corresponding diseases. These studies provide insights into CLN pathogenesis and may guide in designing immuno‐regulatory treatment strategies. GLIA 2016;64:792–809 Main points: Sialoadhesin expression on microglia/macrophages is increased in the CNS of mouse models of CLN disease. Sialoadhesin expression on microglia/macrophages contributes to pro‐inflammatory activation, neural damage and disease outcome. Sialoadhesin expression on microglia/macrophages negatively controls the number of CD8+CD122+ regulatory T‐cells.